INTEGRASI TEORI BELAJAR DALAM PEMBELAJARAN KEJURUAN DI ERA DIGITAL: KAJIAN LITERATUR SISTEMATIS - Octo Ayomy; Ekohariadi Ekohariadi; Rina Harimurti; Heru Arizal; Achmad Imam Agung (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of digital technology, workforce transformation, and the implementation of the Merdeka Curriculum have encouraged the need for vocational learning approaches that produce adaptive, competent, and future-ready graduates. This study aimed to identify the dominant learning theories applied in vocational education at vocational high schools, analyze their implementation in learning practices, and examine their implications for students' competency development. A Systematic Literature Review (SLR) was conducted on ten articles published between 2021 and 2025 that met the inclusion criteria. The findings revealed that constructivism was the most dominant learning theory and was implemented through Project-Based Learning, Problem-Based Learning, Flipped Classroom, and technology-enhanced learning. Experiential Learning, Information Processing Theory, Cognitive Load Theory, and Heutagogy also contributed to contemporary vocational learning. The novelty of this study lies in the Vocational Learning Theory Integration Framework (VLTIF), which integrates the functional roles of the five theories in supporting work readiness and lifelong learning. The findings indicate that vocational education requires an integrative, adaptive, and industry-relevant learning approach to address the challenges of the Society 5.0 era. ABSTRAK Perkembangan teknologi digital, transformasi dunia kerja, dan implementasi Kurikulum Merdeka mendorong perlunya pengembangan pembelajaran vokasi yang mampu menghasilkan lulusan adaptif, kompeten, dan siap menghadapi perubahan. Penelitian ini bertujuan mengidentifikasi teori belajar yang dominan digunakan dalam pendidikan vokasi tingkat Sekolah Menengah Kejuruan (SMK), menganalisis implementasinya dalam proses pembelajaran, serta mengkaji implikasinya terhadap pengembangan kompetensi peserta didik. Penelitian menggunakan metode Kajian Literatur Sistematis (Systematic Literature Review/SLR) terhadap sepuluh artikel yang dipublikasikan pada periode 2021–2025 dan memenuhi kriteria inklusi. Hasil penelitian menunjukkan bahwa konstruktivisme merupakan teori belajar yang paling dominan dan diimplementasikan melalui Project-Based Learning, Problem-Based Learning, Flipped Classroom, serta pembelajaran berbasis teknologi digital. Experiential Learning, Information Processing Theory, Cognitive Load Theory, dan Heutagogy juga berkontribusi dalam mendukung pembelajaran vokasi modern. Kebaruan penelitian terletak pada perumusan Vocational Learning Theory Integration Framework (VLTIF) yang mengintegrasikan fungsi kelima teori dalam mendukung kesiapan kerja dan pembelajaran sepanjang hayat. Temuan ini menunjukkan bahwa pendidikan vokasi memerlukan pendekatan pembelajaran yang integratif, adaptif, dan relevan dengan kebutuhan industri pada era Society 5.0.